IMPLEMENTASI KEBIJAKAN PENERIMAAN PESERTA DIDIK BARU (PPDB) ONLINE TINGKAT SEKOLAH MENENGAH ATAS DI KOTA PEKANBARU TAHUN 2011-2013 - BASOFI SOPIATNO; Hasanuddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
In the early realization PPDB is The students acceptance theimplementation of the program New (PPDB) in Pekanbaru on all levels ofeducation from elementary school until senior high school and vocational schools.However, see the condition that sembrawutan the implementation of the program,the scope has been scaled down only junior secondary schools in and senior highschool and for the schools and vocational training still manually. The purpose ofthis researchis to know there is no policy implementation The students acceptanceinformation system (PPDB) Online high school (SMA) in Pekanbaru in 2011-2013. The method data analysis that is used in this research is descriptivequalitative analysis method that is trying to present based on the phenomena thatare and to all the facts related to problems that discussed based on the results ofresearch policy implementation is The Learners New acceptance (PPDB) onlinehigh school in Pekanbaru in 2011-2013. Results of research menyatakan that thelearners policy implementation acceptance new (PPDB) online high school inPekanbaru year 2011-2013 can be said that it is good enough, this was additionalroutes participants students are participants students (teacher) outside theschool supporting resource, implementation PPDB online high school inPekanbaru fully the responsibility of the Government of the City Pekanbaru, thecommitment and SOUP executive policy only based on rules Mayor ofPekanbaru the students acceptance on guidelines new (PPDB) in primary school,They were accompanied by primary, junior high school, SMPLB, the senior highschool, the Seniour High School, State Vocational School or PrivatePekanbaru and factors that influence policy implementation can be said that it isnot yet walked as expected Because the Government is not enough to carry outPekanbaru socialization PPDB Online especially in high school in Pekanbaru topeople, the Government City of Pekanbaru did not know that the elders parents donot all understand using computers and especially internet, because not allcommunities computer equipment also suggested in his house especially internet.Governments should Pekanbaru through the Education Service Kota Pekanbaru,Jom FISIP Volume 2 No. 1- February 2015 2review whether procedures PPDB online is correct or not, because many parent ofa student who felt harmed register because of their ignorance about internet.Key words : Implementation, PPDB Online, The Senior High School, Pekanbaru.